Role of soluble fms-like tyrosine kinase-1/placental growth factor ratio along with uterine artery Doppler for the prediction of pre-eclampsia – A case–control study - Sathya Jagdish; Kiruthiga T; Shruthi Prashanth; Jaya Vijayaraghavan; Sinduja Thirumanagalam Palanisamy (Asian Journal of Medical Sciences, 2024)
Background: Hypertensive disorders of pregnancy are becoming the leading cause of maternal morbidity and mortality worldwide and are responsible for 9–25% of deaths 1. They are believed to occur due to an imbalance between pro-angiogenic factors, like placental growth factor (PlGF) and anti-angiogenic factors, like soluble fms-like tyrosine kinase-1 (sFLT-1). Aims and Objectives: The aim of the study was to evaluate the role of the sFLT-1/PlGF ratio along with uterine artery Doppler for the prediction of pre-eclampsia (PE). Materials and Methods: The current study was a prospective case–control study conducted at Sri Ramachandra Medical College and Hospital, Chennai, from 2018 to 2020. Blood samples for sFLT-1 and PlGF and uterine artery Doppler were done in 100 pregnant mothers who are at 16–20-week gestation attending antenatal outpatient department in the Department of Obstetrics and Gynecology. Results: We found that the mean sFLT-1 in high-risk group was 826.17 ng/L (standard deviation [SD]±251.31) compared to 924.69 ng/L (SD±360.61) in low-risk groups. The mean PlGF in the high-risk group was 23.07 ng/L (SD±4.68) compared to 27.43 ng/L (SD±5.62) in low-risk group. The mean sFLT-1/PlGF ratio was increased in high-risk group of about 39.68 (SD±22.77) compared to 35 (SD±16.98) in low-risk group. Women with high resistance uterine artery Doppler have 8.5 odds of getting PE compared to those with normal uterine artery Doppler. Conclusion: According to our study, the sFLT-1/PlGF ratio carries more sensitivity (90%) and negative predictive value (74.19%) if we keep the value as 32.25 along with uterine Doppler rather than their individual values for the prediction of PE.